Feto-infantile mortality: causes, evolution and means of combatting - Lelong, Marcel; Alison, François (The Turkish Journal of Pediatrics, 1961)
The struggle against feto-infantile mortality is difficult. There are regions in which almost nothing has been done. In other areas special problems must be resolved. Even in countries with high standards of sanitation one comes up against a residue which is almost irreducible, represented particularly by the prenatal anomalies. In all cases a study of the broad picture of feto-infantile mortality; of the respective importance of each of its constituents; and an investigation of the predominant social factors will prove of great interest, for such studies permit us better to orient our efforts in a domain where important successes can be obtained.